A discussion for integrating INSPIRE with volunteered geographic information (VGI) and the vision for a global spatial-based platform - Demetriou, Demetris; Campagna, Michele; Racetin, Ivana; Konecny, Milan (My University, 2017)
INSPIRE is the EU's authoritative Spatial Data Infrastructure (SDI) in which each Member State provides access to their spatial data across a wide spectrum of data themes to support policy making. In contrast, Volunteered Geographic Information (VGI) is one type of user-generated geographic information where volunteers use the web and mobile devices to create, assemble and disseminate spatial information. There are similarities and differences between SDIs and VGI initiatives, as well as advantages and disadvantages. Thus, the integration of these two data sources will enhance what is offered to end users to facilitate decision makers and the wider community regarding solving complex spatial problems, managing emergency situations and getting useful information for peoples' daily activities. Although some efforts towards this direction have been arisen, several key issues need to be considered and resolved. Further to this integration, the vision is the development of a global integrated GIS platform, which extends the capabilities of a typical data-hub by embedding on-line spatial and non-spatial applications, to deliver both static and dynamic outputs to support planning and decision making. In this context, this paper discusses the challenges of integrating INSPIRE with VGI and outlines a generic framework towards creating a global integrated web-based GIS platform. The tremendous high speed evolution of the Web and Geospatial technologies suggest that this "super" global Geo-system is not far away.
Keywords: Global integrated GIS platform; INSPIRE; SDIs; VGI